Dinamika Konflik dan Penyelesaian Sengketa dalam Perjanjian Kemitraan Usaha Kuliner - Desy Crisyanti; Nurlaily Nurlaily; Triana Dewi Seroja (SIGn Jurnal Hukum, 2023)
This research examines the dynamics of conflict and dispute resolution in culinary business partnership agreements in Batam. This study combines normative and empirical research methods. Primary data collection was done through direct interviews with informants, while secondary data were obtained through a literature review of legal materials. Subsequently, the collected data were analyzed qualitatively to describe the problem and address the research purposes. The results show that the parties still commit breaches of contract within culinary business partnership agreements in Batam. For instance, in the steak franchise partnership case, the receiving partner unilaterally breached the contract with the providing partner by purchasing some of the raw materials from traditional markets. Dispute resolution in culinary business partnership agreements can occur through court and out-of-court proceedings. The T-brand cake business case is an example of dispute resolution at all court levels. Meanwhile, alternative dispute resolution is a method of resolving disputes outside the court proceedings, encompassing various methods such as negotiation, mediation, arbitration, and conciliation. Therefore, it is recommended that the involved parties in culinary business partnership agreements enhance their understanding of dispute resolution methods. Moreover, business actors must ensure they comprehend and comply with the legal provisions in their partnership agreements. In this regard, the government and business associations should play an active role in providing information and training related to dispute resolution and valid partnership agreements, as well as ensuring that fair business policies and practices are implemented in the culinary business sector in Batam.